2020
DOI: 10.3390/cancers12102795
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Y-Box Binding Protein-1 through Simultaneous Targeting of PI3K and MAPK in Triple Negative Breast Cancers

Abstract: The multifunctional protein Y-box binding protein-1 (YB-1) regulates all the so far described cancer hallmarks including cell proliferation and survival. The MAPK/ERK and PI3K/Akt pathways are also the major pathways involved in cell growth, proliferation, and survival, and are the frequently hyperactivated pathways in human cancers. A gain of function mutation in KRAS mainly leads to the constitutive activation of the MAPK pathway, while the activation of the PI3K/Akt pathway occurs either through the loss of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 61 publications
(85 reference statements)
1
9
0
Order By: Relevance
“…However, it inhibited AKT (S473) phosphorylation in MDA-MB-231, with relatively lower levels of AKT phosphorylation shown in Fig. S 1 and reported before [ 36 ]. In HSF-7 normal human fibroblast, fisetin slightly inhibited YB-1 (S102) phosphorylation only at concentrations of 25 and 50 µM (Fig.…”
Section: Resultssupporting
confidence: 72%
“…However, it inhibited AKT (S473) phosphorylation in MDA-MB-231, with relatively lower levels of AKT phosphorylation shown in Fig. S 1 and reported before [ 36 ]. In HSF-7 normal human fibroblast, fisetin slightly inhibited YB-1 (S102) phosphorylation only at concentrations of 25 and 50 µM (Fig.…”
Section: Resultssupporting
confidence: 72%
“…Previous studies have demonstrated that activation of the signaling pathway depends on the mutation status of cell lines. MDA-MB231 cells harbor KRAS­(G13D) and BRAF­(G464V) mutations that lead to the hyperactivation of the MAPK/ERK pathway in association with the suppression of Akt phosphorylation. Hs 578T cells harbor an HRAS­(G12D) mutation that leads to the hyperactivation of both the PI3K/Akt and MAPK/ERK pathways . CD44 regulation affected distinct signaling pathways, indicating that even if it is expressed at a similar level in the two claudin-low breast cancer cell lines, its functions might depend on the difference in the genetic background and origin.…”
Section: Resultsmentioning
confidence: 99%
“…The Y Box binding protein 1 (YB1) is a multifunctional protein, found both in the cytoplasm and inside the nucleus, that belongs to the highly conserved Cold Shock Domain protein family [ 16 ]. Among its multitude of functions, YB1 is more known to be involved in the regulation of transcription, mRNA stability, and splicing [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. More recently, YB1 was found to play key roles in the regulation of tumor development, progression and metastasis, as well as drug resistance in several cancers, including the ones generated in the breast [ 17 , 24 , 26 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among its multitude of functions, YB1 is more known to be involved in the regulation of transcription, mRNA stability, and splicing [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. More recently, YB1 was found to play key roles in the regulation of tumor development, progression and metastasis, as well as drug resistance in several cancers, including the ones generated in the breast [ 17 , 24 , 26 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. In this study, we show that dysregulated YB1 expression to be associated primarily with breast cancer cell lines in primary tumors of the TNBC subtype as compared to their luminal or HER2+ counterparts.…”
Section: Introductionmentioning
confidence: 99%